Use and abuse of amphetamine-type stimulants in the United States of America - G. Cajetan Luna (Revista Panamericana de Salud Pública, 2001)
In recent years the United States of America has experienced economic growth, low unemployment, low inflation, and technological advances. However, coexisting with these favorable conditions are underlying and underaddressed social inequalities that may have an impact on patterns of use and abuse of substances, including amphetamine-type stimulants (ATSs). For example, since 1975 most of the increase in national income has benefited people who are at the top 20% of the income range. There are disparities between those who do have and those who do not have the skills needed to thrive in a technologically dependent society, and the gap may be widening. New patterns of substance abuse being seen in the United States may in part be explained by the increasing competition to survive financially and interpersonally, the need that those failing to adapt to rapid technological change have to escape psychologically and existentially, and the desire of the socially alienated and disenfranchised to self-medicate with ATSs and at least temporarily avoid social and economical inequities. According to the 1998 National Household Survey on Drug Abuse, an estimated 13.6 million Americans were users of illicit drugs (1). This number is less than the 13.9 million estimated for 1997, and by comparison less than the highest level, in 1979, when the estimate was 25 million. With respect to stimulants in particular, the overall level of usage has remained constant, but increases have been observed in specific high-risk populations, who need focused outreach and intervention efforts. This article will focus on ATSs in the United States, including relevant demographic and cultural dimensions of their use and abuse, and suggested directions for future ATS research and program development.